Social Media and Content Analysis Critical Discourse Analysis of Kuali Merah Putih Episode 3 Content on Bobon Santoso's YouTube Channel - Rifal Ramadhan; Khaerudin Imawan; Rahmayanti (SEULANGA SYSTEM PUBLISHER, 2025)
The content of the Red and White Cauldron video on the Bobon Santoso YouTube Channel on March 5, 2024, is entitled